Hospital Outbreak of Middle East Respiratory Syndrome Coronavirus - Assiri, Abdullah; McGeer, Allison; Perl, Trish M; Price, Connie S; Al Rabeeah, Abdullah A; Cummings, Derek A.T; Alabdullatif, Zaki N; Assad, Maher; Almulhim, Abdulmohsen; Makhdoom, Hatem; Madani, Hossam; Alhakeem, Rafat; et al. (The New England journal of medicine, 2013)
A novel coronavirus (MERS-CoV) is causing severe disease in the Middle East. In this report on a hospital outbreak of MERS-CoV infection, 23 confirmed cases and evidence of person-to-person transmission were identified. The median incubation period was 5.2 days. Respiratory viruses are an emerging threat to global health security and have led to worldwide epidemics with substantial morbidity, mortality, and economic consequences. Since the severe acute respiratory syndrome (SARS) pandemic in 2003–2004, 1 – 3 two additional human coronaviruses — HKU-1 and NL-63 — have been identified, both of which cause mild respiratory infection and are distributed worldwide. 4 , 5 In September 2012, the World Health Organization (WHO) reported two cases of severe community-acquired pneumonia caused by a novel human β-coronavirus, subsequently named the Middle East respiratory syndrome coronavirus (MERS-CoV). 6 – 8 Since then, MERS-CoV has been identified as the cause of pneumonia . . .